Failure of the Nemo Trial: Bumetanide Is a Promising Agent to Treat Many Brain Disorders but Not Newborn Seizures - Ben-Ari, Yehezkel; Damier, Philippe; Lemonnier, Eric (Frontiers in Cellular Neuroscience, 2016)
The diuretic bumetanide failed to treat acute seizures due to hypoxic ischemic encephalopathy (HIE) in newborn babies and was associated with hearing loss (NEMO trial; 1). On the other hand, clinical and experimental observations suggest that the diuretic might provide novel therapy for many brain disorders including autistic spectrum disorder, schizophrenia, Rett syndrome and Parkinson disease. Here, we discuss the differences between the pathophysiology of severe recurrent seizures in the neonates and neurological and psychiatric disorders stressing the uniqueness of severe seizures in newborn in comparison to other disorders.